The Effectiveness of School Principals in Making Decisions on Professional Teacher Performance to Increase Student Success at School - Amelia, Amelia; Sembiring, Ari Wibowo; Hasibuan, Elsa Elitia; Tanjung, Laila Ali; Harahap, Yusuf Ali Ahmad; Darmansah, T (Continuous Education: Journal of Science and Research, 2023)
This journal article aims to discuss the effectiveness of school principals in making decisions regarding professional teacher performance in order to increase student success at school. The data collection technique in this journal uses the method used is library research, in this case the effectiveness of the school principal, namely; 1) able to empower teachers to carry out the learning process well, smoothly and productively, 2) able to complete assignments and work according to the specified time, 3) able to establish harmonious relationships with the community so that they can actively involve them in realizing school goals and education, 4) successfully implementing leadership principles that are appropriate to the maturity level of teachers and other employees at the school, 5) working with the management team, and 6) successfully realizing school goals in a productive manner in accordance with established provisions. For this reason, the effectiveness of the principal's leadership is very important in improving the quality and achievements of the school.